+0

# plz help asap tysm

+1
310
11 I know it's a lot but can you please help me >.<

Sep 11, 2018

#1
+2

15.  -3x ( 5x + 1) (8 - 2x)  =

-3x ( 5x * 8 + 1*8 - 2x*5x - 2x*1) =

-3x ( 40x + 8  - 10x^2  - 2x)  =

-120x^2  - 24x  + 30x^3  + 6x^2  =

30x^3 - 114x^2  - 24x   Sep 11, 2018
#2
+1

ty but the others are different i still find it hard to understand >.<

RainbowPanda  Sep 11, 2018
#4
+1

Working on them  one at a time, RP....give me a few....   CPhill  Sep 11, 2018
#5
0

I'm working on 18 right now can you gelp with 19 and 20?

RainbowPanda  Sep 11, 2018
#3
+1

I might be able to do the rest not so sure about 19 and 20 tho

Sep 11, 2018
#6
+1

16. (a + b)(3a - b)(2a + 7b) =
(3a² - ab + 3ab - b²)(2a + 7b) =
(3a² + 2ab - b²)(2a + 7b) =
6a³ + 21a²b + 4a²b + 14ab² - 2ab² - 7b³ =
6a³ + 25a²b + 12ab² - 7b³
Explanation: Multiply any two terms first, in this case I multiplied (a+b) and (3a-b) first. Then with the result, multiply it with the last term.
17/18 follows the same procedure as 16.

19. (-42x¹⁰y⁵+12x⁸y³-6x²y) / (6x²y) =
[(-42x¹⁰y⁵) / (6x²y)] + [(12x⁸y³) / (6x²y)] + [(-6x²y) / (6x²y)]
(-7x⁸y⁴) + (2x⁶y²) + (-1)
-7x⁸y⁴ + 2x⁶y² - 1
Explanation: Separate the fraction into 3 fractions. Simplify using division and laws of exponents.
20 follows the same procedure as 19.

Sep 11, 2018
#7
+1

Thank you! ^-^

RainbowPanda  Sep 11, 2018
#9
0

I got the set up part done but not sure how to do this >.<

[(16a^4/12a^3)]-[(40a^2/12a^3)]+[(24a/12a^3)]

RainbowPanda  Sep 11, 2018
#10
+1

aˣ/aʸ = aˣ⁻ʸ

For (16a⁴/12a³)], you can separate out the numbers and the variable so you get:
16/12 times a⁴/a³.
Think of 16/12 as a fraction and reduce it to its lowest terms --> 4/3
Same for a⁴/a³ --> a⁴⁻³ --> a
Put them back together and you get 4a/3

For [(40a^2/12a^3)], separate to 40/12 times a²/a³.
40/12 --> 10/3
a²/a³ --> a²⁻³ --> a⁻¹ --> 1/a
Put them together --> 10/3a

For [(24a/12a^3)], separate to 24/12 times a/a³.
24/12 --> 2
a/a³ --> a¹⁻³ --> a⁻² --> 1/a²
Put them together --> 2/a²

So, we get
(4a/3) - (10/3a) + (2/a²)

We can make it neater by keeping the denominators the same. The LCM is 3a².
Multiply 4a/3 by a²/a² to get 4a³/3a².
Multiply 10/3a by a/a to get 10a/3a².
Multiply 2/a² by 3/3 to get 6/3a².

Now, we can turn the expression into a single fraction.
(4a³/3a²) - (10a/3a²) + (6/3a²) --> (4a³-10a+6)/(3a²)

Guest Sep 11, 2018
#11
+1

Alternatively, we can factor out the common term on the numerator.
(16a⁴-40a²+24a)/12a³

Factor out 8a:
8a(2a³-5a+3)/12a³

From here we can separate the fraction into 8a/12a³ times (2a³-5a+3)
8a/12a³ --> 2/3a²

Put them back together --> 2(2a³-5a+3)/3a²

Distribute the 2 --> (4a³-10a+6)/3a²

Guest Sep 11, 2018
#8
+2

16

(a + b)(3a - b) (2a + 7b)      expand the first two factors

( 3a *a + 3ab - ab - b^2) (2a  + 7b) =     simplify the terms in the left parentheses

(3a^2 + 2ab - b^2)(2a + 7b)  =    expand the first terms over the second

3a^2 * 2a  +  2ab * 2a -  b^2* 2a   + 3a^2* 7b +  2ab*7b - b^2*7b   =

6a^3 + 4a^2b - 2ab^2 + 21a^2b + 14ab^2 - 7b^3   =

6a^3 + 25a^2b + 12ab^2 - 7b^3   Sep 11, 2018